NEPHROPROTECTIVE EFFECT OF LYCOPENE IN HYPERGLYCEMIA INDUCED OXIDATIVE STRESS IN MALE WISTAR RATS - V., AKILANDESWARI; M., Sekkizhar; A., Sylvia Santhakumari; P., Nirmala (International Journal of Current Pharmaceutical Research, 2015)
Objective: Diabetes mellitus is the chronic metabolic disorder characterized by chronic hyperglycemia associated with absolute or relative deficiency in insulin secretion or insulin action. The most commonly accepted cause of diabetes is the oxidative damage that is caused by free radicals generation. Free radicals have high ability to attract electrons from macromolecules such as carbohydrates, protein, lipid and DNA. Excessive Reactive oxygen species (ROS) can cause structural deterioration and instability of the macromolecules, consequently affecting proper cellular signaling pathways, gene regulation and function. The present study was conducted to investigate the nephroprotective effect of lycopene in alloxan induced type I diabetes. Methods: Male wistar rats were divided in to 5 groups 6 in each. Group1 as control, Group II. III,IV and V were diabetic groups. Group II diabetic control, Group III treated with protamine zinc insulin 0.9 u/100 gm s. c. Group IV and V treated with 2.5 mg/kg and 5 mg/kg of lycopene. After 3 weeks blood samples were collected from all the groups of animals to measure Lipid peroxidation. Serum glucose, urea and creatinine. Results: The serum Glucose, urea and creatinine were significantly increased in untreated diabetic rats. In addition, there was significant rise in lipid peroxidation. Conclusion: In this study, oxidative damage with diabetes was ameliorated with administration of lycopene. The results of this study indicate that lycopene is an effective nutritional component to alleviate or prevent the complications.